2017
DOI: 10.1119/1.4974122
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of High School Physics Teachers for Female Students’ Physics Identity and Persistence

Abstract: Given the historic and continued underrepresentation of women in physics, it is important to understand the role that high school physics might play in attracting female students to physics careers. Drawing on data from over 900 female undergraduates in physics, we examine when these women became interested in physics careers and different sources of recognition (important for physics identity development) that may have affected their choices at certain time points. The results provide optimism since many of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 10 publications
3
49
0
2
Order By: Relevance
“…In quantitative studies of mathematics and physics identity, recognition was found to have the strongest direct effect on students seeing themselves as a math or physics person (Cribbs et al, 2015;Godwin et al, 2016). Physics recognition also strongly predicts students' intentions to persist in physics careers (Hazari, Brewe, Goertzen, & Hodapp, 2017;Lock, Hazari, & Potvin, 2013).…”
Section: Early Stem Recognition and Identitymentioning
confidence: 95%
See 1 more Smart Citation
“…In quantitative studies of mathematics and physics identity, recognition was found to have the strongest direct effect on students seeing themselves as a math or physics person (Cribbs et al, 2015;Godwin et al, 2016). Physics recognition also strongly predicts students' intentions to persist in physics careers (Hazari, Brewe, Goertzen, & Hodapp, 2017;Lock, Hazari, & Potvin, 2013).…”
Section: Early Stem Recognition and Identitymentioning
confidence: 95%
“…Being seen as a science person, for example, enables or limits whether a student sees her/himself as a “science person.” In quantitative studies of mathematics and physics identity, recognition was found to have the strongest direct effect on students seeing themselves as a math or physics person (Cribbs et al, ; Godwin et al, ). Physics recognition also strongly predicts students’ intentions to persist in physics careers (Hazari, Brewe, Goertzen, & Hodapp, ; Lock, Hazari, & Potvin, ). Qualitative work insightfully reveals that the accumulation of recognition experiences from others contributes to the identity trajectories of individuals and whether they envision a future self in science (Barton et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These young students are in their adolescence and thus move through a developmental period where they discover and develop their (gendered) identities [72,73]. In this developmental stage, adolescents consolidate their commitments to life plans and projects [73,74], and young women build their motivation to become physicists [75]. Besides the academic strength of the young women in the intervention and their potential to excel in physics, these students tend to be affected by messages from the social environment (e.g., ability stereotypes) [76].…”
Section: Research Questionsmentioning
confidence: 99%
“…Moreover, prior research has revealed that high school physics teachers are positioned to attract students to physicsrelated careers, including students who were not previously interested in physics. Surveys of more than 900 female physics undergraduates showed that female students are attracted to physics (from other career interests) during high school at more than double the rates than during middle school or college [6]. In addition, both male and female teachers have been found to be equally effective in attracting female students to science, including physics [7].…”
Section: Introductionmentioning
confidence: 99%